Dissociative Identity Disorder Potrayed By Malcolm Rivers In The “Identity” Movie By James Mangold - aliya aliya; dian mukhlisa; firdiansyah fir (English Language, Linguistics, Literature, And Education Journal, 2020)
Kinds and cause of dissociative identity disorder experienced by Malcolm as the main character in a movie entitled Identity. The purpose of writing this research is to analyze and find out what kinds of dissociative identity disorder and what are the causes of dissociative identity disorders. This research uses psychologycal approach by Wellek and Warren, Paulette M. Gillig about dissociative identity disorder, and the theory of kinds of dissociative identity disorder by Nevid, theory of the cause of dissociative identity disorder by Thomas Oldmans. The method used in analyzing the problem in this thesis is a qualitative descriptive method. The results of this study are that Malcolm experienced dissociative identity disorder, he has ten other personalities in him and there are four kinds of dissociative identity disorder that Malcolm had, they are: the main personality, the dominant personality, the dissociative identity which there is no connection between the personality and the dissociative identity which there is connection between the personality. The cause of DID experienced by Malcolm is Psychological factor where he remembered what happened when in the past and he could not forget it that was why he want to be independent.